In silico investigations and potential approaches of Tectona grandis via targeting MMP-9 for triple negative breast cancer - Permana, Sofy; Hanum, Halida A.; Azizah, Maghfira R.; Ilmiyah, Silvi Z.; Permana, Aiko Z.; Norahmawati, Eviana; Widodo, Edwin; Fakurazi, Sharida; Kawamoto, Yoshiyuki; Endharti, Agustina T. (Faculty of Pharmacy, University of Benin, 2024)
The limited treatment options for triple-negative breast cancer are attributed to the absence of hormone receptor and human epidermal growth factor receptor 2 gene expression. There is a growing need to explore novel therapeutic drugs or combination therapies that can enhance the efficacy of Triple Negative Breast Cancer. Tectona grandis, with its antioxidant properties and potential health benefits, holds promise in cancer prevention and therapy. The objective of this research is to evaluate the potential of the bioactive substances of T. grandis as cancer drugs. The matrix metalloproteinase-9 structure was obtained from Protein Data Bank, while the substances derived from T. grandis were sourced from various existing studies and screened using PASS database, Lipinski’s rule of five, and Veber rule. The molecular docking was performed using PyRx and visualized using PyMOL. ProteinsPlus and LigPlus were used to visualize the interaction between protein and ligand in a diagram. Twelve active substances of T. grandis leaves (butyl acetate, 4-hydroxy-4-methyl-2-pentanone, glycerin monoacetate, glycerin diacetate, methyl decanoate, sinapic acid, gallic acid, ferulic acid, P-coumarate, cinnamic acid, vanillic acid, and quercetin) show potential as anticancer agents based on PASS screening from Lipinski's rule of five and Veber rule. Among these, quercetin (-10), gallic acid (-7.3), and ferulic acid (-7.3) demonstrate the lowest binding energies according to molecular docking. Notably, quercetin exhibits the most favorable activity potential in PASS screening for both anticarcinogenic (0.757/0.007) and antineoplastic especially against breast cancer (0.577/0.012). Quercetin demonstrated the highest potential to work as a Matrix Metalloproteinase-9 inhibitor.